As long as you love me - Aguirre, Ann (Aguirre, Ann. 2B trilogy, 2014)
After flunking out of college and losing her scholarship, twenty-one-year-old Lauren Barrett returns home to Nebraska where she finds an ally in Rob Conrad, her best friend's older brother, and together they try to figure out their futures.